2016
DOI: 10.1016/j.cct.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Treatment of Abdominal Aortic Aneurysm Clinical Trial (N-TA 3 CT): Design of a Phase IIb, placebo-controlled, double-blind, randomized clinical trial of doxycycline for the reduction of growth of small abdominal aortic aneurysm

Abstract: Objectives The Non-Invasive Treatment of Abdominal Aortic Aneurysm Clinical Trial (N-TA3CT) is a Phase IIb randomized, placebo-controlled clinical trial, testing doxycycline (100 mg bid) for inhibition of growth in the greatest transverse, orthogonal diameter of small abdominal aortic aneurysms (AAA). Methods We will enroll 258 patients, ≥ 55 years of age who have AAA, men: 3.5–5.0 cm and women: 3.5–4.5 cm on CT scans confirmed centrally. The primary outcome is growth in maximal transverse, orthogonal diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Our analysis revealed that 45.0% of patients underwent elective AAA repair at less than the recommended 5.5 cm diameter threshold. In frail patients, 35.6% underwent EVAR and 22.2% underwent OAR with aneurysms measuring <5.5 cm. The Society for Vascular Surgery Clinical Practice Guidelines recommend elective repair for patients at low or acceptable surgical risk with a fusiform AAA that is 5.5 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis revealed that 45.0% of patients underwent elective AAA repair at less than the recommended 5.5 cm diameter threshold. In frail patients, 35.6% underwent EVAR and 22.2% underwent OAR with aneurysms measuring <5.5 cm. The Society for Vascular Surgery Clinical Practice Guidelines recommend elective repair for patients at low or acceptable surgical risk with a fusiform AAA that is 5.5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…33 Development of medical therapies for slowing AAA growth, such as the ongoing work in doxycycline and metformin, also has the potential to produce a paradigm shift in our management of AAAs, especially for frail patients. 34,35 Age and comorbidities are associated with poor outcomes but are not useful as tools for determining candidacy for surgery given the heterogeneity of outcomes. 36,37 Frailty, however, has consistently been shown to predict poor outcomes, and more evidence continues to accumulate that frailty is multidimensional and goes beyond merely comorbidities and functional status.…”
Section: Discussionmentioning
confidence: 99%
“…106,115 Currently, another clinical trial with a higher dosage of doxycycline is underway in the U.S. and its results are anticipated. 11 Further, AAA patients undergoing treatments with nonsteroidal anti-inflammatory drugs, diuretics, mast cell inhibitors, β blockers, calcium channel blockers, and ACE inhibitors have not exhibited any noteworthy accomplishments. 17,57,155 Other concerns about oral medication therapy for AAA include limitations with respect to current AAA animal models, correct drug dosage, etc .…”
Section: Pgg As a Potential Therapeutic Option For Aaa Patientsmentioning
confidence: 99%
“…2 Although pharmaceuticals such as doxycycline are currently in trial for AAA treatment, no FDA approved medical treatment currently exists for those who do not qualify for operative repair. 3 While the etiology of AAA formation and growth is unclear at this time, we do know that an intense local inflammatory response leads to the eventual loss of vessel wall integrity. 4 The therapeutic benefit of mesenchymal stem cells (MSCs) in pathologies with substantial inflammatory responses such as graft vs host disease (GVHD), chronic obstructive pulmonary disease (COPD), and myocardial remodeling after infarction are well established.…”
Section: Introductionmentioning
confidence: 99%